Thrifting Consumer Communication Experience in Yogyakarta - Rachmalia Hasna Savryaninda; Vani Dias Adiprabowo (Jurnal Indonesia Sosial Sains, 2024)
Thrifting, the increasingly popular activity of shopping for used clothes, came under scrutiny when the government banned the import of used goods. This study aims to analyze thrifting consumer communication experiences regarding prohibiting imports of used goods and their impact on local industries. In the phenomenological approach, the researcher explores the meaning of thrifting consumers' experiences related to popular culture and wasteful behavior. Studies show that thrifting as a shopping alternative can help overcome the problem of turning off expensive and low-quality local goods. This is because thrifting provides foreign goods at lower prices and good quality. Even so, the issue of local products of inferior quality and expensive remains an obstacle that must be overcome. Possible solutions include improving the quality of local products, providing education and information to the public, and improving the quality of thrifting services and products. Thus, this problem can be overcome with solutions from the government, local producers, and consumers so that it can positively impact the economy and the environment.